2007
DOI: 10.1359/jbmr.070802
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration Is Regulated by Wnt Signaling

Abstract: Tissue regeneration is increasingly viewed as reactivation of a developmental process that, when misappropriated, can lead to malignant growth. Therefore, understanding the molecular and cellular pathways that govern tissue regeneration provides a glimpse into normal development as well as insights into pathological conditions such as cancer. Herein, we studied the role of Wnt signaling in skeletal tissue regeneration.Introduction: Some adult tissues have the ability to regenerate, and among these, bone is one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
201
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(206 citation statements)
references
References 60 publications
(104 reference statements)
4
201
0
1
Order By: Relevance
“…Importantly, levels of functional Dkk1 predict protection from syndesmophyte formation in patients with AS [18]. Moreover, adenoviral overexpression of Dkk1 was shown to strongly reduce bone healing in mouse, in association with a complete prevention of Runx2 expression and TNAP activity [37]. However, in our hands, Dkk1 failed to reproducibly inhibit TNAP or mineralization.…”
Section: Discussionmentioning
confidence: 53%
“…Importantly, levels of functional Dkk1 predict protection from syndesmophyte formation in patients with AS [18]. Moreover, adenoviral overexpression of Dkk1 was shown to strongly reduce bone healing in mouse, in association with a complete prevention of Runx2 expression and TNAP activity [37]. However, in our hands, Dkk1 failed to reproducibly inhibit TNAP or mineralization.…”
Section: Discussionmentioning
confidence: 53%
“…(8) Conversely, inhibition of the Wnt/b-catenin pathway by adenoviral overexpression of Dickkopf 1 has been shown to inhibit the fracture healing process. (8)(9)(10) These results suggest that agents that activate the Wnt/b-catenin signaling pathway may have the potential to improve fracture healing.…”
Section: Introductionmentioning
confidence: 91%
“…By modulating Wnt signaling, it is possible to achieve an anabolic effect in bone. Skeletal trauma causes a local increase in Wnt signaling [11] and it has been shown that the pathways involved in bone Wnt signaling are necessary for bone healing [11][12] and for bone formation in general [13][14][15]. Fracture repair can be influenced by blocking Dkk1 in mice [16] and a decrease in Dkk1 gene expression leads to an increase in bone mass and strength [15,17].…”
Section: Introductionmentioning
confidence: 99%